1998
DOI: 10.1001/archsurg.133.7.740
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Iron Supplementation After Roux-en-Y Gastric Bypass

Abstract: To determine whether prophylactic oral iron supplements (320 mg twice daily) would protect women from iron deficiency and anemia after Roux-en-Y gastric bypass.Design: Prospective, double-blind, randomized study in which 29 patients received oral iron and 27 patients received a placebo beginning 1 month after Roux-en-Y gastric bypass.Setting: Tertiary care medical center.Patients and Interventions: Complete blood cell count and serum levels of iron, total iron binding capacity, ferritin, vitamin B 12 , and fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
17

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(87 citation statements)
references
References 9 publications
1
67
0
17
Order By: Relevance
“…In case series lasting 1 to 8 years, iron deficiency developed in 20% to 49% of GBP patients; it was most likely to occur in menstruating women (114 -116). Data show that 640 mg/d of ferrous sulfate can prevent iron deficiency (117) and that the addition of vitamin C to iron supplements can improve absorption in GBP patients (118). Vitamin B 12 deficiency has been found in 25% to 75% of GBP patients after WLS.…”
Section: Micronutrientsmentioning
confidence: 99%
“…In case series lasting 1 to 8 years, iron deficiency developed in 20% to 49% of GBP patients; it was most likely to occur in menstruating women (114 -116). Data show that 640 mg/d of ferrous sulfate can prevent iron deficiency (117) and that the addition of vitamin C to iron supplements can improve absorption in GBP patients (118). Vitamin B 12 deficiency has been found in 25% to 75% of GBP patients after WLS.…”
Section: Micronutrientsmentioning
confidence: 99%
“…With specific iron supplementation, iron deficiency anemia may be prevented (as assessed by adequacy of ferritin levels) but mild anemia can still result, despite normal vitamin levels. 51 This finding highlights the concern that some nutritional risks of gastric bypass may be usual and expected, whereas others may not necessarily fit with expected physiologic paradigms.…”
Section: Nutritional Risks Of Weight Loss Surgerymentioning
confidence: 93%
“…While standard multivitamins may prevent folate and B12 depletion, Brolin, Gorman, Milgrim, and Kenler (1991) found that multivitamin supplementation did not adequately prevent iron deficiencies and anemia in post-RYGB patients (Brolin et al, 1991). In a subsequent randomized, double blind controlled trial of menstruating women who had undergone RYGB, Brolin et al (1998) found that supplementation twice daily with oral ferrous sulfate effectively prevented iron deficiency in patients adherent to taking the prescribed supplements, although 20% of this sample abandoned iron supplementation because of unpleasant gastrointestinal side effects (Brolin et al, 1998).…”
Section: Clinical Presentationmentioning
confidence: 99%